Corroboration of a Major Role for Herpes Simplex Virus Type 1 in Alzheimer’s Disease - Itzhaki, Ruth F. (Frontiers in Aging Neuroscience, 2018)
Strong evidence has emerged recently for the concept that herpes simplex virus type 1 (HSV1) is a major risk for Alzheimer's disease (AD). This concept proposes that latent HSV1 in brain of carriers of the type 4 allele of the apolipoprotein E gene (APOE-e4) is reactivated intermittently by events such as immunosuppression, peripheral infection, and inflammation, the consequent damage accumulating, and culminating eventually in the development of AD. Population data to investigate this epidemiologically, e.g., to find if subjects treated with antivirals might be protected from developing dementia - are not available in the UK or in most other countries. However, in Taiwan, the National Health Insurance Research Database, in which 99.9% of the population has been enrolled, is being extensively mined for information on microbial infections and disease. Three publications have now appeared describing data on the development of senile dementia (SD), and the treatment of those with marked overt signs of disease caused by varicella zoster virus (VZV), or by HSV. The striking results include evidence that the risk of SD is much greater in those who are HSV-seropositive, and that antiviral treatment causes a dramatic decrease in number of subjects who later develop SD. It should be stressed that these results apply only to those with presumed severe cases of HSV1 or VZV infection which are rare, but when considered with the over 130 publications that strongly support an HSV1 role in AD, they greatly justify usage of antiherpes antivirals to treat AD. Three other studies are relevant, even though none directly concerns AD. One compared certain cognitive features of HSV-infected and uninfected schizophrenia patients, and used valacyclovir (VCV) , a potent anti-herpes antiviral agent, to treat them. The second study used a combination of an antiherpes agent with a Cox-2 inhibitor, to treat fibromyalgia patients, on the basis that the disease is caused by reactivated HSV1 The third study examined the risk of later development of SD in fibromyalgia patients. Studies on the link between epilepsy, AD, and HSE are described also, as are the possible roles of APOE-e4, HHV6 and HSV1 in epilepsy.